The lncRNA LOC100257036 and vvimiR156 modulate gibberellin signaling through AGAMOUS during cluster formation in Sistan Yaghooti grape - Shahla Sahraei; Nafiseh Mahdinezhad; Abbasali Emamjomeh; Kaveh Kavousi; Mahmood Solouki; Massimo Delledonne (Scientific Reports)
Abstract The long non-coding RNAs (lncRNAs), despite lacking the ability to encode proteins, have become essential players in regulating gene expression in crops. Yaghooti grape in addition to its good flavor, is highly regarded by consumers due to its high nutritional value. However, the compact clusters and small berries are notable features that negatively impact its marketability. Gibberellin is widely used to reduce cluster density. This research aimed to identify lncRNAs involved in cluster formation and examine how their expression is influenced by gibberellin treatment. The expression of lncRNAs is spatiotemporally specific, and external stimuli can influence their expression. However, the role of lncRNA in modulating the transcriptional pathway of gibberellin is unknown. The length of grape clusters increased from 107 to 184 mm under gibberellin treatment, accompanied by a corresponding decrease in cluster density. RNA-seq data related to Sistan Yaghooti grape clusters were examined at three stages of formation and in response to gibberellin to identify lncRNA transcripts. A total of 2021 lncRNAs were identified, of which 262 lncRNAs showed differential expression. The numbers of lncRNAs and target genes that exhibited significant differential expression were 76, 100, and 86 lncRNAs and 146, 143, and 138 target genes, respectively, in stage2 vs. stage1, stage3 vs. stage2, and stage3 vs. stage1. The target genes of lncRNAs were significantly associated with (Catabolic Process, hydrolase activity, Phosphorylation, ATP binding, response to abiotic stimulus). Furthermore, pathway analysis indicated that majority of genes in the treated samples were primarily linked to metabolic pathways and secondary metabolite biosynthesis in comparison to the control group. Specifically, genes such as cytokinin (CK), Indole-3-acetic acid (IAA), squamosa-promoter binding protein-like2 (SPL2), LATERAL ORGAN BOUNDARIES DOMAIN (LBD), Domain of Unknown Function 1218 (DUF1218), the non-specific phospholipase C2 (NPC2), Cytochrome P450 (P450 CYP), pectin methylesterases (PMEs), and AGAMOUS (AG) showed significantly increased expression in response to gibberellin. Some of these genes are targets of lncRNAs that interact with microRNAs (miRNAs) vvi-miR156, vvi-miR159, vvi-miR172, and vvi-miR319. Among the differentially expressed non-coding RNAs, lncRNA LOC100257036 and vvi-miR156 may contribute to gibberellin-mediated regulation of AG, potentially influencing cluster architecture through a lncRNA–miRNA–mRNA regulatory pathway.